2021
DOI: 10.1029/2020ja028930
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sprite Current and Morphology

Abstract: • Optically-large sprites with upward streamers (carrots and jellyfish) tend to have larger sprite current moments than column sprites • 63 sprites were detected using up to 100,000 fps high-speed video. VLF remote sensing shows that 56% of them have a sprite current signature • Several vigorously luminous sprites have remarkably large peak current moments, up to 2,700 kA km

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
(92 reference statements)
1
10
0
Order By: Relevance
“…Similar collisions in sprites were reported by Montanyà et al (2010, Figure 4) and Stenbaek-Nielsen et al (2013, Figure 7). Very complex behavior of sprite streamers (recorded at 100,000 frames per second), including collisions, was reported by McHarg et al (2019) (see also Contreras-Vidal et al, 2020).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Similar collisions in sprites were reported by Montanyà et al (2010, Figure 4) and Stenbaek-Nielsen et al (2013, Figure 7). Very complex behavior of sprite streamers (recorded at 100,000 frames per second), including collisions, was reported by McHarg et al (2019) (see also Contreras-Vidal et al, 2020).…”
supporting
confidence: 52%
“…Very complex behavior of sprite streamers (recorded at 100,000 frames per second), including collisions, was reported by McHarg et al. (2019) (see also Contreras‐Vidal et al., 2020).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…An analysis of the 63 sprites and their relation to sprite currents has been presented by Contreras‐Vidal et al. (2021). The two carrots are relatively weak compared to most of the 63 sprites, and Contreras‐Vidal et al., extracted no sprite currents for the event.…”
Section: Data and Analysismentioning
confidence: 99%
“…Li et al (2012) also suggested that the timescale of causative CG strokes, primarily the impulse current, has a significant impact on the morphology of sprites (e.g., Qin et al, 2013). First of all, as shown in Figure 3 regarding one of the cases examined in details by Li et al (2012), due to the relatively short duration and therefore a less influence by the relatively high conductivity at high altitudes, the lightning-induced E-field perturbation can penetrate into higher region; secondly, the short duration of charge transfer results in a greater induction component in the lightning-induced E-field perturbation (e.g., Contreras-vidal et al, 2021), and therefore the overall region of dielectric breakdown extends to a higher altitude.…”
Section: Negative Sprites Produced By Continental Thunderstormsmentioning
confidence: 96%